Sustainable development goals in health courses in higher education - Chaleta, E; Saraiva, M.; Semedo, C.; Nogueiro, T. (Management in Hhgher education for sustainability, 2025)
The fact that health is responsible for about 4.4% of global greenhouse gas emissions led us to analyse the mapping of the SDGs in the Health courses of a higher education institution in order to find out whether the concern is present in the type of SDGs marked by teachers. The data presented refer to the SDGs marked by teachers in the course units, with the exception of SDG4 (Quality Teaching) previously marked by the university. The results showed that the objectives most marked by teachers in all courses were SDG3 (Ensure healthy lives and promote well-being for all at all ages) and SDGlO (Reduce inequality within and among countries). We found that there are no differences between the SDGs reported in the three study cycles and that the data indicate the need for greater awareness of those involved in undergraduate and postgraduate training with a view to training models more focused on sustainability.